Elim : a cultural historical study of a Moravian mission station at the Southern extreme of Africa - Van der Hoven, Liane (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MA (Afrikaans Cultural History))--University of Stellenbosch, 2001.